(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2021)
This study focuses on political dimensions of India-China relations. It starts with defining what political relationship is and how it is different from other relationships. The historical backdrop traces the evolution of India-China ties from ancient trade routes to modern geopolitical interactions. India-China relations have achieved comprehensive improvement and cooperation in the areas of politics, trade and commerce, technology and culture etc. The talks between the two leaders established the basis for the improvement of India-China relations. Both countries reached at a point where they understand their boundary issue was the only obstacle between the two countries and agreed to settle down through peacefully and friendly negotiations. Both parties examined all aspects of their bilateral ties, from the political to the strategic to the economic & cultural. India & China’s bilateral, sub-regional, and regional ties present an opportunity to reorganize their collaboration, which would have positive effects on all three levels.